Collaborative research in healthcare: uncovering the impact of industry collaboration on the service innovativeness of university hospitals - Thomas Huynh (The Journal of Technology Transfer, 2024)
In the face of the challenges of rising demand and increasing economic pressure, medical service innovations and university hospitals are becoming increasingly important as cornerstones for the continuous development of medical care. Simultaneously, increasing technological complexity, scarce funding, and resource-intensive technology development are forcing university hospitals to open up their internal innovation processes. Numerous studies have highlighted the beneficial effects of cross-sectoral collaboration on the innovation performance of industrial entities, while neglecting the perspective of academic institutions. The impact of industry collaborations on the service innovativeness of university hospitals in particular has not been addressed in previous research. Although the potential for nonlinear effects of university-industry collaborations has been discussed in research, adequate evidence, particularly in the healthcare context, has not been provided. Therefore, this study addresses the questions: (1) What is the impact of university-hospital-industry collaboration (UHIC) on the service innovativeness of university hospitals? (2) Can a nonlinear relationship between UHIC and university hospitals' service innovativeness be empirically verified? The hypotheses are tested based on an unbalanced panel data set, which combines three distinct data sources and comprises annual observations from 2011 until 2019 of all German university hospitals. The findings indicate that the UHIC intensity has a positive effect on university hospitals' service innovativeness with a one-year time lag. Furthermore, a negative quadratic UHIC effect was found. In doing so, this study complements existing research and opens the black box by uncovering the downside of cross-sectoral collaboration for a more complete understanding of the underlying dynamics of this growing area of research, with a particular focus on university hospitals.
Keywords: O30; O32; I19; 600; University hospital; University-industry collaboration; Service innovativeness; Research collaboration; Knowledge transfer